Efectividad del cerclaje cervical vs progesterona vaginal en la prevención de parto pretérmino en gestantes con insuficiencia cervical en el Hospital Belén de Trujillo durante el periodo Enero 2010 – Enero 2022 - Torres Moreno, Wilson Martín (2022)
Preterm birth is defined as a birth that occurs after 20 weeks of gestation and before 37 completed weeks, associated with a high risk of neonatal morbidity and mortality, however, it is a problem for public health worldwide, since It carries short-term and long-term neonatal complications. It accounts for approximately 70% of perinatal mortality and 75% of morbidity, and its incidence can range from 5% in some European countries to 18% in some African countries. Spontaneous onset of preterm labor can be due to multiple causes, including cervical incompetence as a reason for preterm labor or even early pregnancy loss. The latter is the inability of the cervix to maintain its structure and function to maintain pregnancy. The clinical management of this cervical dysfunction is based on the restriction of the mother's activity, the administration of progesterone, the successive measurements of the cervix by ultrasound, the placement of a pessary or the performance of a cervical cerclage. However, the administration of progesterone and cervical cerclage are the ones that have shown greater efficacy over the years. Cervical cerclage is the surgical intervention that consists of the application of a suture of non-absorbable material in the cervix in order to keep the internal cervical orifice closed. Progesterone is a cholesterol-derived steroid hormone, which may act to counteract inflammatory pathways, leading to preterm labor and birth by acting as a key inhibitor of prostaglandins and proinflammatory cytokines at the maternal-fetal interface. Considering that there are no well-established therapeutic measures to control the risk of preterm delivery, we believe that it is extremely important to find the best treatment and that it has better validation.